Performance of EDM die-sinking parameters on material characteristics of LM6 using graphite electrode - Noorhaslina Azani (2019)
Nowadays, EDM die-sinking is one of the important processes to produce a product made from a hardness material with a close tolerance. EDM die-sinking process works effectively for machining deep holes and micro holes with high accuracy.In this study, graphite electrode used to machine aluminium alloy LM6 as a work piece. Full factorial method was used as a design of experiment in order to run the matrix order. To get the significant parameters and optimize the parameters to optimum level, ANOVA analysis is needed. The objective of this project is to study the performance of die sinking parameters on material characteristics by using graphite as electrode. The input responses of this study are current, pulse on time and pulse off time. The output responses that need to measured are material removal rate (MRR), electrode wear rate (EWR) and surface roughness (Ra). From the experimental result, current is the most significant parameters that give an effect to all the three responses which are material removal rate, electrode wear rate and surface roughness. Besides, the combination of current factor with other factors such as pulse on time and pulse off time also give an effect to the responses. The higher current with high pulse on is needed to get a maximum MRR. It is find that current contribute 61.28% followed by pulse on time 1.07% and pulse off time 0.89%. for MRR. While a lower current result an optimum or lower EWR. Current factor contribute 39.16% followed by pulse on time with 15.13% and pulse off time 2.89% affect the response. The value of Ra is also depending on current and pulse on time value so current contribute 76.61%, pulse on time 19.41% and pulse off time 17.36%. The lower current and pulse on can produce a fine surface during machining. Based on the main effect plot ranking, for all the three responses show that current is the most affected factors to the responses followed by pulse on time and pulse off time.